Using DNA Immunization to Elicit Monoclonal Antibodies in Mice, Rabbits, and Humans - Liu, Shuying (Hum Gene Ther, 2018)
In recent vaccine studies, DNA immunization was found to effectively stimulate both innate and adaptive immunities to elicit high levels of antigen-specific antibody responses. The DNA molecule itself can activate multiple pathways of innate immunity. The in vivo production of antigens allows for presentation by major histocompatibility complexes, so that T-cell responses are generated to help in the development of antigen-specific B cells, leading to high-affinity antibody response. By using the same process, DNA immunization should also be effective at producing functionally potent monoclonal antibodies (mAbs). Furthermore, the in vivo expressed proteins can maximally maintain the native structures and go through appropriate post-transcriptional modifications. By combining such advantages, DNA immunization can be expected to play more important roles in the future to elicit mAbs against difficult targets from a wide range of host systems. The current report shares our group's experience in using DNA immunization to elicit mAbs in the mouse, rabbit, and human models.